ANALISIS HUBUNGAN EFIKASI DIRI DAN KEMAMPUAN LITERASI DIGITAL DENGAN HASIL BELAJAR SIMULASI DIGITAL - Cahyono; Soeprijanto; Priyono (LPPM, Universitas Negeri Jakarta, 2021)
The research objective was to analyze the positive relationship between self-efficacy and digital literacy skills, both together and independently, with digital simulation learning outcomes. The population in this study were all students of SMK Taman Harapan 1 Bekasi in the 2020/2021 academic year. Sampling was done by random sampling as many as 72 students from four expertise programs. The digital simulation learning outcome instrument uses a test while the self-efficacy instrument and digital literacy skills use a non-test in the form of a Likert scale. The research hypothesis was tested using correlation and multiple regression. The results show that: 1) There is a positive relationship between self-efficacy and digital simulation learning outcomes, 2) there is a positive relationship between digital literacy skills and digital simulation learning outcomes, and 3) there is a positive relationship between self-efficacy and digital literacy together with Digital Simulation learning outcomes. The conclusion of this research is that self-efficacy and digital literacy skills are positively related to Digital Simulation learning outcomes, both together and independently. Thus, the higher the self-efficacy and digital literacy skills of the students, the higher the learning outcomes of digital simulation for students of SMK Taman Harapan 1 Bekasi. Keywords: Self-Efficacy, Digital Literacy, Learning Outcomes, Digital Simulation